Treatment options for epilepsy during pregnancy. Issue 6 (November 2005) - Biraben, Arnaud; Beauplet, Anne
Women with epilepsy of childbearing age account for a third of the epilepsy population and about one in 200 pregnant women take antiepileptic drugs (AEDs). Although 90 to 95% of these women have an uneventful pregnancy with normal delivery of a healthy child (vs. 98% in the general population) there is a two to threefold greater risk of fetal malformation. The risk depends on the number of AEDs used and the type and dose of the drug –– the risk appears higher with high doses of valproate than with older AEDs, such as carbamazepine and newer AEDs such as lamotrogine, but there is currently insufficient data on many of them. A familial history of malformation increases the risk but apparently not the number of seizures during pregnancy. Sudden interruption of AEDs can be life threatening for the fetus and the mother if withdrawal status epilepticus develops. More recently, psychomotor retardation has been observed in some infants born to women with epilepsy. Pregnancy in these women must be planned and monitored by a neurologist and an obstetrician.